PENGARUH MERENDAM KAKI DENGAN AIR HANGAT TERHADAP KUALITAS TIDUR PADA PASIEN RAWAT INAP DI UPT. PUSKESMAS DUNGKEK KECAMATAN DUNGKEK - Moch Mochlis andriyadi (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2016)
Sleep is a basic need that must be met by humans. Sleep disorders can lead to serious problems and even reduce quality of life. This often occurs in hospitality that decrease the quality of sleep. Soaking the feet in warm water can improve the microcirculation of the blood vessels and vasodilation causing a relaxing effect, followed by increased secretion of melatonin thus improving the quality of sleep. This study aimed to identify the effect of soaking feet in warm water to the quality of sleep of patient in the PUSKESMAS Dungkek This study uses a quasi-experimental design approach to one group pretest-posttest. The sampling technique used purposive sampling with 20 respondents who had been in accordance with the inclusion and exclusion criteria. Intervention is given for 3 consecutive days. Measurement of sleep quality scores using the Pittsburgh Sleep Quality Index questionnaire. Differences in sleep quality scores were analyzed by d using the Wilcoxon test. The results showed the influence of soaking feet in warm water for sleep quality before and after the intervention p=0.001 (<0.005), from these results it mean an increase in the quality of sleep after a soak feet in warm water. This study is expected to be an alternative option for nurses to apply soak feet in warm water to improve the quality of sleep of patient in hospital.